Firm Performance of Banks and Tax Planning (International Journal of Innovative Research in Engineering & Management, 2021)
Understanding how the banking industry  works is essential because it has ramifications across the  economy. The link between bank profitability and tax  planning efforts in a developing country is examined in this  research. Non-financial business performance and tax  preparation have also shown to have a neutral relationship,  according to experts in the field. There is also no  relationship between company performance and tax  preparation. In particular, people examine at how  corporation tax, business size, liquidity, leverage, firm age,  and firm growth affect the return on assets (ROA) of  India's listed banks. The study uses data from all eight  listed banks on the Indian Stock Exchange (ISE) from 2015  to 2019. For the analysis of our study, people used the ordinary least squares (OLS) regression model. There is a  link between bank performance and business tax  preparation, according to our findings. People urge bank  CEOs to examine and manage their tax burden in order to  improve their profitability.
Keywords: Corporate; Firm Performance; India Stock Exchange; Study